Prenatal diagnosis of fetomaternal hemorrhage by a novel hydrogel fluoroimmunoassay that accurately quantifies fetal haemoglobin - Li, Xinyang; Yin, Moli; Wang, Hongmei; Duan, Shengbao; Wang, Huiyan; Li, Yong; Liu, Tiemei (Frontiers in Bioengineering and Biotechnology, 2023)
Abstract Background Fetomaternal hemorrhage (FMH) is an alloimmunization resulting from the incompatibility of fetal and maternal blood. For the prevention of newborn haemolytic disease (HDN), it is crucial to quantify the amount of fetomaternal hemorrhage. However, the classical Kleihauer–Betke test (K-B test) for detecting fetomaternal hemorrhage is constrained by experimental tools and conditions and is not suitable for routine clinical use. Therefore, the method of prenatal diagnosis of fetomaternal hemorrhage applicable to the clinic is a subject deserving of further investigation. Therefore, it is worthwhile to further investigation on the clinically applicable prenatal diagnosis method for fetomaternal hemorrhage. Methods In this experiment, the ability of hydrogel to separate sensitised red blood cells (RBCs) from soluble antibodies is demonstrated. Using flow cytometry (FCM), the fluorescence values of sensitised red blood cells and fluorophore-labeled antibodies were measured, and the test steps for the detection products of a novel technology were determined. The properties of a hydrogel fluoroimmunoassay were evaluated by distinguishing between the amounts of fetal and adult haemoglobin. Comparing this technology to the Kleihauer–Betke test, its precision is evaluated. Results This experiment evaluated adult (n=2) and fetal (n=6) haemoglobin fluorescence detection results. At the same time, the fluorescence intensity of different fetal haemoglobin(HbF) in adult haemoglobin(HbA) was calculated. The fluorescence value was 1.6% at 0.1%. Conclusions The novel hydrogel fluoroimmunoassay can accurately determine the fluorescence intensity by flow cytometry to differentiate fetal haemoglobin from adult haemoglobin, quantitatively prenatally diagnose fetal haemoglobin, address the incompatibility between fetal and maternal blood types, and prevent alloimmunization.